ETIKA PESERTA DIDIK DALAM PENDIDIKAN ISLAM (TELAAH TERHADAP KITÂB AL-’ILM KARYA MUHAMMAD SALIH AL-’USAIMIN) - Ihsan Fauzi Dalimunthe (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2018)
This research, intended to know how the ethics of learners and factors that affect the success and failure of learners according to Muhammad Salih al-Usaimin. This research is literature study by using text analysis. The results showed that: 1) Ethics of students is sincere intention, eradicate the ignorance, defend of Islam, tolerant, practice science, knowledge, be role models, be patient, respect the clergy, hold fast, thorough and consistent, and careful in understanding Qur'an and Hadith. 2) The factors driving success is piety, diligence, memorization, and mulazamah al-Ulama. While the inhibiting factor is spite, taqwa, knowledge, takabbur, fanatic, appear before mastering the material, and prejudiced bad.